Venom Costs and Optimization in Scorpions - Evans, Edward R. J.; Northfield, Tobin D.; Daly, Norelle L.; Wilson, David T. (Frontiers in Ecology and Evolution, 2019)
Scorpions use venoms as weapons to improve prey capture and predator defence, and these benefits must be balanced against costs associated with its use. Venom costs involve direct energetic costs associated with the production and storage of toxins, and indirect fitness costs arising from reduced venom availability. In order to reduce these costs, scorpions optimise their venom use via evolutionary responses, phenotypic plasticity, and behavioural mechanisms. Over long timescales, evolutionary adaptation to environments with different selection pressures appears to have contributed to interspecific variation in venom composition and stinger morphology. Furthermore, plastic responses may allow scorpions to modify and optimise their venom composition as pressures change. Optimal venom use can vary when facing each prey item and potential predator encountered, and therefore scorpions display a range of behaviours to optimise their venom use to the particular situation. These behaviours include varying sting rates, employing dry stings, and further altering the volume and composition of venom injected. Whilst these cost-reducing mechanisms are recognised in scorpions, relatively little is understood about the factors that influence them. Here, we review evidence of the costs associated with venom use in scorpions and discuss the mechanisms that have evolved to minimise them.